Pengaruh Manajemen Perubahan Terhadap Organisasi Pembelajaran Serta Dampaknya Terhadap Kinerja Pegawai Pada PT. KAI (Persero) Daop II Bandung - Joeliaty Joeliaty; Yayan Firmansyah (Jurnal Manajemen dan Bisnis Indonesia, 2016)
Changes of business environment that is increasingly fast encountered by PT.KAI (PERSERO) DAOP II Bandung. It requires this company to be adapted. Adapting with this is condition is a must. The company's ability to address the challenges of current and future become one of the power that must be owned by the company. The purpose of this research is to discover to discover effect change management on learning organization and its implication on employee performance in PT.KAI (PERSERO) DAOP II Bandung. This research used survey method by distributing questionnaires to 100 respondents. The result of Effect of change management on employee performance through learning organization is about 41.11%. Keywords : change management, learning organization, employee performance